Selective laser sintering of carbon nanotube–coated thermoplastic polyurethane: mechanical, electrical, and piezoresistive properties - Zhou, Meixin (2023)
Flexible and electrically conductive carbon nanotube/thermoplastic polyurethane (CNT/TPU) nanocomposites have been herein fabricated by selective laser sintering (SLS) for the applications of wearable electronics and strain sensors. CNT/TPU nanocomposite powders were systematically developed by a latex-based technique. The effects of CNT content on the SLS processability of nanocomposite powders and the mechanical, electrical, and piezoresistive properties of SLS-printed specimens were investigated. It was found that the CNT improved the electrical conductivity and strain sensing performance of the printed parts, but excessively high CNT content led to high melt viscosity, deteriorated sintering behavior, and hence degraded mechanical properties. The 2.0 wt% CNT/TPU nanocomposite fabricated by SLS exhibited enhanced electrical conductivity (seven orders of magnitude higher than the neat TPU), high piezoresistive sensitivity (gauge factor of 60 at a tensile strain of 20%), and a wide sensing range (0‒130% strain). A mathematical model based on the tunneling theory was established to describe and predict the strain sensing performance of the printed nanocomposites. This study provides profound insights into the development of multi-functional nanocomposites by SLS for their applications in flexible strain sensors.